Patriotyzm w nauczaniu Kościoła katolickiego - Przesmycki SDB, ks. Piotr (Annales. Etyka w Życiu Gospodarczym, 2008)
In nearly every modern society, patriotism, as a form of love related to one’s homeland, possesses its own specific semantic colours. This is so due to historical and cultural differences between nations. In recent debates about the condition of patriotism in Poland as well as political disputes, patriotism is often mentioned as, alongside with others, a civilian virtue. According to various research on public opinions, patriotism is recognised as one of the most distinctive characteristics of the Poles (beside religiousness and resourcefulness). It is a virtue as well as an attitude which Poles manifest in various ways (from the so-called “football” patriotism to simple daily work solidly done with honesty and diligence for the good of one’s homeland). This paper presents a conception of patriotism from the Catholic Social Teaching viewpoint. This teaching, taking into account both Divine Revelation and past experiences of mankind (the socalled “hermeneutical arch” of Moral Theology, perceives the phenomenon of patriotism in a wider context such as nation, homeland, country and international community). The Church insists on upbringing and education of love towards one’s homeland, while distances its teaching clearly and decisively from racial prejudice and hypernationalism (cf. Ad Gentes, 15).